2022
DOI: 10.1371/journal.pbio.3001761
|View full text |Cite
|
Sign up to set email alerts
|

Functional architecture of pancreatic islets identifies a population of first responder cells that drive the first-phase calcium response

Abstract: Insulin-secreting β-cells are functionally heterogeneous. Whether there exist cells driving the first-phase calcium response in individual islets, has not been examined. We examine “first responder” cells, defined by the earliest [Ca2+] response during first-phase [Ca2+] elevation, distinct from previously identified “hub” and “leader” cells. We used islets isolated from Mip-CreER; Rosa-Stop-Lox-Stop-GCamP6s mice (β-GCamP6s) that show β-cell-specific GCamP6s expression following tamoxifen-induced CreER-mediate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Most recently, studies used viral transduction approaches to clamp maturity across the islet showed a reduction in hub cell number and a decrease in coordinated activity, thus confirming the validity of the previous studies using an unbiased approach and extending the concept to the entire immature beta cell subclass (288). Similar beta cell subpopulations have been described that are capable of disproportionate control of islet function, including first responder cells (222), as well as ChR2.0 cells (447), and it is likely that there is some overlap between such populations and hubs/leaders. Pertinently, FLIM imaging supports the existence of hub-like cells that metabolically recruite other cells into oxidative phosphorylation (442).…”
Section: Syncytial Beta Cell Functionsupporting
confidence: 69%
See 2 more Smart Citations
“…Most recently, studies used viral transduction approaches to clamp maturity across the islet showed a reduction in hub cell number and a decrease in coordinated activity, thus confirming the validity of the previous studies using an unbiased approach and extending the concept to the entire immature beta cell subclass (288). Similar beta cell subpopulations have been described that are capable of disproportionate control of islet function, including first responder cells (222), as well as ChR2.0 cells (447), and it is likely that there is some overlap between such populations and hubs/leaders. Pertinently, FLIM imaging supports the existence of hub-like cells that metabolically recruite other cells into oxidative phosphorylation (442).…”
Section: Syncytial Beta Cell Functionsupporting
confidence: 69%
“…However, numerous studies have shown that Ca 2+ signals within the islets obey a power-law distribution, i.e. a hub and node setup (203,222,254,360,396,397), which goes against the established electrophysiological theory that all cells are similar by virtue of their coupling, despite known heterogeneity in cell traits and 65 even gap junction permeability itself (37,124). For example, recent optogenetic/photopharmacological studies have shown that a small subpopulations of beta cells might also contribute to coordinated islet responses to glucose (203,447).…”
Section: Syncytial Beta Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not identify changes in transcripts encoding proteins previously demonstrated by others to 'mark' specific beta cell subpopulations such as Flattop/Cfap126 (26), CD9 and ST8SIA1 (20), 'virgin' beta cells (via Ucn3) (34) or those differentially-expressed in beta cells implicated in the control of Ca 2+ dynamics ('hubs' (24), and 'leaders' (25,35)).…”
Section: Nnat + and Nnatbeta Cells Have Distinct Transcriptional Sign...mentioning
confidence: 75%
“…In β-cells, in particular, both glucose-stimulated cytosolic Ca 2+ and the downstream insulin secretion depend on the cell having an intact, motile primary cilium, as evidenced by experimental models of IFT88-mediated cilia deletion and dynein-mediated cilia dysmotility ( Hughes et al, 2020 ; Cho et al, 2022 ). β-cells are heterogeneous in their cytosolic Ca 2+ response, with distinct subsets of cells exhibiting higher levels of excitability or functional connectivity ( Johnston et al, 2016 ; Westacott et al, 2017 ; Salem et al, 2019 ; Dwulet et al, 2021 ; Kravets et al, 2022 ). Targeted ablation or inhibition of these functional nodes can perturb whole-islet Ca 2+ oscillations, suggesting that there may be cells capable of driving neighboring cell Ca 2+ dynamics and thereby coordinating pulsatile insulin secretion ( Johnston et al, 2016 ; Westacott et al, 2017 ; Salem et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%